Individual incentives in supervised work groups: from human subject experiments to agent based simulation. (6th February 2009) - Dal Forno, Arianna; Merlone, Ugo
We consider a model of work group interaction and introduce an incentive scheme in order to prevent dissatisfaction in subordinates. Several behaviours, which are grounded on observing human subjects when interacting in a similar task, are implemented in artificial agents and simulated. Our results shed light on some aspects of interaction between individuals in complex environment and economic performance, and give insights in terms of observation of the performance measures in organisations.